Bridging indigenous knowledge and scientific evidence for pharmacological studies of phaleria macrocarpa: a systematic review - Mia, Abdur Rashid; Ferdosh, Sahena; Ahmed, Qamar; Abul Bashar Mohammed, Helaluddin; Sarker, Md. Zaidul Islam (Bentham Science, 2021)
Background: Phaleria macrocarpa (Scheff.) Boerl. (Thymelaeaceae), usually referred to as God’s crown, Mahkota dewa, Pau, grows all year long in tropical countries, including Malaysia, Indonesia, Papua New Guinea, and Australia. It is traditionally used to treat haemorrhoids, stroke, heart disease, tumour, impotence, diabetes, allergies, kidney and liver disorders, migraine, acne, and skin ailments.